Current criteria for selecting cochlear implant in deaf patients: a review - Swain, Santosh Kumar (International Journal of Advances in Medicine, 2021)
Cochlear implantation is indicated in patients with severe to profound hearing loss that cannot be adequately treated by other auditory rehabilitation measures. The definitive indication of cochlear implantation is made on the basis of an extensive interdisciplinary clinical, audiological, radiological, and psychological diagnostic work-up. There are numerous changes are happening in cochlear implant candidacy. These have been associated with concomitant changes in surgical techniques, which enhanced the utility and safety of cochlear implantation. Currently, cochlear implants are approved for individuals with severe to profound unilateral hearing loss rather than previously needed for bilateral profound hearing loss. Studies have begun using the short electrode arrays for shallow insertion in patients with low-frequency residual hearing loss. The advancement in designs of the cochlear implant along with improvements in surgical techniques reduce the complications and result in the safety and efficacy of the cochlear implant which further encourages the use of these devices. This review article aims to discuss the new concepts in the candidacy of the cochlear implant, cochlear implant in younger children and hearing preservation, a cochlear implant for unilateral deafness, bilateral cochlear implant, and cochlear implant with neural plasticity and selection of patients for the cochlear implant.